(untitled) (Global Journal of Human-Social Science, 2025)
This research explores whether any misinformation regarding women is being spread in the Waj Mahfils of Bangladesh through social media platforms At present an extensive number of people are listening to these Waj Mahfils using social media platforms and therefore fabricated information about women can have a terrible impact on society Waj Mahfils held in Bangladesh and conducted by so-called Islamic speakers of this country Shaykh Abdur Razzaq Bin Yusuf Abu Twha Muhammad Adnan Shah Ahmed Shafi and Amir Hamza have been selected from YouTube and Facebook as purposive sample for this research Representation theory has been chosen as the theoretical framework It can be expected that through this research people will get a clear idea about the fake speakers of Islam and their false speeches on various social economic and marital issues of women It will also be a helpful tool for future researchers in this regard